Arginase II Promotes Intervertebral Disc Degeneration Through Exacerbating Senescence and Apoptosis Caused by Oxidative Stress and Inflammation via the NF-κB Pathway - Li, Fudong; Sun, Xiaofei; Zheng, Bing; Sun, Kaiqiang; Zhu, Jian; Ji, Chenglong; Lin, Feng; Huan, Le; Luo, Xi; Yan, Chen; Xu, Jiashun; Hong, Yun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Intervertebral disc degeneration (IDD) has been generally accepted as the major cause of low back pain (LBP), which imposes massive clinical and socioeconomic burden. Previous studies demonstrated that oxidative stress and inflammatory response induced senescence and apoptosis of nucleus pulposus cells (NPCs) are the main cellular processes that cause IVDD. ARG2 (arginase II), an enzyme involved in a variety of pathological processes including cellular senescence, apoptosis, oxidative stress, and inflammation, showed promoting degeneration effect on a series of degenerative diseases such as osteoarticular diseases. Based on previous studies, we hypothesized that ARG2 deficiency might be conductive to the therapy of IDD by inhibiting the dyshomeostasis of ECM and the oxidative stress and inflammatory response induced senescence and apoptosis via NF-κB. In this study, the data revealed that ARG2 deficiency inhibited the senescence and apoptosis of NPCs and degeneration of ECM induced by oxidative stress and inflammatory response. Similar results were also observed with the selective NF-κB pathway inhibitor JSH-23. In contrast, overexpression of ARG2 produced opposite consequences. Taken together, our results suggest that ARG2 deficiency prevents IDD via NF-κB, indicating an effective therapeutic method for IDD.